Corazon ang unang aswang - Gonzales, Erich; Ramsay, Derek; Gil, Mark
"A woman desperately wants to have a baby because she believes this will fully make her and her husband happy. She did every possible means to get pregnant, even resorting to miracles. After months of sacrifice, she gave birth to a dead baby. Thus, the start of the deterioration of her faith and sanity. And life in the small town changed."